PEMBIAYAAN MURABAHAH DALAM PERNYATAAN STANDAR AKUNTANSI KEUANGAN (PSAK) NO. 102 - Sholikah, Amaliatus (IAIN Tulungagung, 2014)
This article discusses the murabaha (resale with an advance) financing contained in the Statement of Financial Accounting Standards (SFAS) No. 102. Murabaha financing has been described in SFAS no. 102, which contains the scope, definitions, characteristics, recognition and measurement, accounting for the final buyer, disclosure, terms of the transaction, and the effective date of the withdrawal. The discussion focuses on the characteristics of murabaha, because the characteristics are the foundation of the murabaha financing. In addition, characteristics will also be able to present an overview of the murabaha contract, which is not shared by the other contractagreement.Kata kunci: Pembiayaan Murabahah, PSAK No. 102